Structural Parameters Optimization of R&(2-RPR)+UPS Parallel Mechanical Legs - Li Zhen; Wang Xiaolei; Li Xiaodan (Jixie chuandong)
Aiming at the problem of small workspace in the majority of parallel robotic legs, a novel R&(2-RPR)+UPS parallel mechanical leg with an amplification mechanism is proposed, and its main structural parameters are optimized. Firstly, the three-dimensional models of the parallel mechanical leg and the whole quadruped robot are established by SolidWorks software. The position inverse solution of the single leg mechanism is derived, and its correctness is verified through simulations using Adams and Matlab software. Secondly, the workspace volume of the single leg is computed by Monte Carlo method and used as the optimization index. The rules between the optimization index and various structural parameters are studied separately, and the optimization variables are determined. Finally, the main structural parameters of the robotic leg are optimized by the particle swarm optimization algorithm. The results show that the optimized robotic leg's workspace volume is increased by 69.83%, and the workspace ranging in X and Y directions are increased respectively by 35.26% and 19.51%, which has improved the quadruped robot's ability of fast walking and obstacle overcoming.